Inhibitory effects of mefenamic acid on rat urinary bladder contractions in vitro - Kacar, Emine; Yılmaz, Seçil; Serhatlioglu, İhsan; Oz, Zeynep Dila; Hekım, Munevver Gizem; Bozyil, Ahmed Sait; Ercan, Zubeyde (My University, 2024)
Aim: In this study, the effect of mefenamic acid, a nonsteroidal anti-inflammatory drug, on the unconstrained contractile movement of the bladder muscle of female Spraque Dawley rats in diestrus was investigated. Since the effect of mefenamic acid on bladder smooth muscle is not known and its use for other conditions may cause possible side effects on the bladder, its effect was investigated for the possibility of using it as an active substance in the treatment of bladder problems. Materials and Methods: In the experimental study, 1.5 cm long smooth muscle strips from seven female Sprague Dawley rats were prepared and suspended in an isolated organ bath system containing Krebs solution under 1.5 g tension. The system was gassed continuously with oxygen/carbon dioxide mixture (95%:5%) and isometric contractions were recorded. At a dose of 300 µM, the contraction/relaxation effects of mefenamic acid concentration on bladder smooth muscle were investigated. The area under the curve (AUC) and amplitude values of bladder contractions were analyzed before and after mefenamic acid administration. With the data obtained from the analysis, the effect of mefenamic acid on bladder contractions was evaluated using paired t-tests in SPSS Statistical Software. Results: The decrease in area and amplitude values was statistically significant (p<0.05). Mefenamic acid had an inhibitory effect on bladder contractions. Conclusion: The present findings demonstrate the relaxant effect of mefenamic acid on the rat bladder and if similar effects are observed in human studies, mefenamic acid may be effective in the treatment of voiding problems such as bladder incontinence.
Keywords: Urinary bladder; Mefenamic acid; Isolated organ bath; Female rat